(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In this paper I examine various performance environmentsfrom the point of a specific body. I take six different types of bodies: thebody mapped, the body governed, the body connected, the body assaulted, thebody pivotal, and the body breathless. I commence with what I title the bodymapped. This body is derived from the neurobiological findings ofneuroscientist and philosopher Antonio Damasio.